2013
DOI: 10.1038/srep02040
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Streptococcus pneumoniae pilus-1 undergoes on and off switching during colonization in mice

Abstract: Streptococcus pneumoniae pili contribute to adherence and virulence. The regulation of pilus-1 expression is bistable, thus piliated strains contain a variable proportion of pilus-1-non-expressing bacteria. We investigated whether such proportion changes during colonization. Pilus-1-expressing bacteria were quantified in nasopharyngeal washes and pharyngeal tissues from mice that received intranasally bacterial populations with high (H), medium (M) or low (L) pilus-1 expression rates. In nasopharyngeal washes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…It is interesting that the expression of ebp pili and orthologous pili in other Gram-positive pathogens is tightly controlled (9). It has been suggested that a bistable switch mechanism may control the expression of streptococcal pili, such that individual cells are either "on" or "off" (29,30). An electron microscopic analysis of OG1RF suggests that a similar expression pattern may occur for ebp pili in OG1RF (7).…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting that the expression of ebp pili and orthologous pili in other Gram-positive pathogens is tightly controlled (9). It has been suggested that a bistable switch mechanism may control the expression of streptococcal pili, such that individual cells are either "on" or "off" (29,30). An electron microscopic analysis of OG1RF suggests that a similar expression pattern may occur for ebp pili in OG1RF (7).…”
Section: Discussionmentioning
confidence: 99%
“… Pili : these hair-like structures are located on the cell surface of S. pneumoniae and many other bacteria ( 27 , 51 , 81 ). They assist with S. pneumoniae’s attachment and colonization of epithelial cells within the nasopharynx and lungs of hosts ( 51 , 81 , 82 ). These pili also help the bacteria avoid phagocytosis by host immune cells ( 22 ).…”
Section: Virulence Factorsmentioning
confidence: 99%
“…However, ectopic expression of FHA during the Bvg − phase was not sufficient to promote adherence in vivo (20), underscoring the importance of tight control over adhesin expression for effective colonization. Similarly, pilus expression in pneumococci appears to be regulated, as it peaks during the early phases of murine colonization (86). …”
Section: Acquisition and Attachmentmentioning
confidence: 99%